Purpose in life in emerging adulthood: Development and validation of a new brief measure. Issue 3 (3rd May 2016) - Hill, Patrick L.; Edmonds, Grant W.; Peterson, Missy; Luyckx, Koen; Andrews, Judy A.
Abstract : Accruing evidence points to the value of studying purpose in life across adolescence and emerging adulthood. Research though is needed to understand the unique role of purpose in life in predicting well-being and developmentally relevant outcomes during emerging adulthood. The current studies (total n  = 669) found support for the development of a new brief measure of purpose in life using data from American and Canadian samples, while demonstrating evidence for two important findings. First, purpose in life predicted well-being during emerging adulthood, even when controlling for the Big Five personality traits. Second, purpose in life was positively associated with self-image and negatively associated with delinquency, again controlling for personality traits. Findings are discussed with respect to how studying purpose in life can help understand which individuals are more likely to experience positive transitions into adulthood.